T1R3 homomeric sweet taste receptor regulates adipogenesis through Gαs-mediated microtubules disassembly and Rho activation in 3T3-L1 cells - Masubuchi, Yosuke; Nakagawa, Yuko; Medina, Johan; Nagasawa, Masahiro; Kojima, Itaru; Rasenick, Mark M.; Inagaki, Takeshi; Shibata, Hiroshi (PloS one, 2017)
We previously reported that 3T3-L1 cells express a functional sweet taste receptor possibly as a T1R3 homomer that is coupled to Gs and negatively regulates adipogenesis by a Gαs-mediated but cAMP-independent mechanism. Here, we show that stimulation of this receptor with sucralose or saccharin induced disassembly of the microtubules in 3T3-L1 preadipocytes, which was attenuated by overexpression of the dominant-negative mutant of Gαs (Gαs-G226A). In contrast, overexpression of the constitutively active mutant of Gαs (Gαs-Q227L) as well as treatment with cholera toxin or isoproterenol but not with forskolin caused disassembly of the microtubules. Sweetener-induced microtubule disassembly was accompanied by activation of RhoA and Rho-associated kinase (ROCK). This was attenuated with by knockdown of GEF-H1, a microtubule-localized guanine nucleotide exchange factor for Rho GTPase. Furthermore, overexpression of the dominant-negative mutant of RhoA (RhoA-T19N) blocked sweetener-induced dephosphorylation of Akt and repression of PPARγ and C/EBPα in the early phase of adipogenic differentiation. These results suggest that the T1R3 homomeric sweet taste receptor negatively regulates adipogenesis through Gαs-mediated microtubule disassembly and consequent activation of the Rho/ROCK pathway.